2014
DOI: 10.1007/s00431-014-2285-7
|View full text |Cite
|
Sign up to set email alerts
|

Improving influenza surveillance in Portuguese preschool children by parents’ report

Abstract: Influenza surveillance is usually based on nationally organized sentinel networks of physicians and on hospital reports. This study aimed to test a different report system, based on parents' phone contact to the research team and in home collection of samples by a dedicated team. The identification of influenza and other respiratory viruses Communicated by David NadalWhat is new in your paper on the basis what is already known in the field? Influenza surveillance in Europe is based mainly on nationally organiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…Results of chronic respiratory diseases and quality of life from this project have already been published (Carreiro-Martins et al, 2016). The team involved was the same of a previous one that studied the health impact of indoor air environment in Children Day Care Centers (ENVIRH) (Araújo-Martins et al, 2014;Paixão et al,2014).…”
Section: Introductionmentioning
confidence: 99%
“…Results of chronic respiratory diseases and quality of life from this project have already been published (Carreiro-Martins et al, 2016). The team involved was the same of a previous one that studied the health impact of indoor air environment in Children Day Care Centers (ENVIRH) (Araújo-Martins et al, 2014;Paixão et al,2014).…”
Section: Introductionmentioning
confidence: 99%
“…Participatory influenza surveillance systems were often found to be comparable [32,40] or, in a few instances, superior to existing sentinel surveillance systems [29,35] in providing advanced warning of seasonal influenza activity. However, while these systems were reported to have high sensitivity for influenza detection, their specificity may be variable depending on the syndromic definition of ILI used.…”
Section: Discussionmentioning
confidence: 99%
“…Fifteen studies analysed the utility of the participatory system and reported multiple uses, apart from collecting epidemiological data on the ILI incidence. The systems allowed access to specific populations, such as children [19,29,30], pregnant women [31], and healthcare workers [21], and access to information on healthcare-seeking behaviour [16,32,33]. Participatory systems like FluWatchers or FluTracking were used to collect information about vaccination uptake and effectiveness [16,34], while the School Health Surveillance System (SHSS) system was designed to provide data on school absenteeism [30].…”
Section: Attributes Of Participatory Surveillance Systemsmentioning
confidence: 99%
See 1 more Smart Citation